Update on classification of oncocytic neoplasms of the kidney. Issue 3 (20th May 2023) - Oszwald, André; Wasinger, Gabriel; Zisser, Lucia; Compérat, Eva
Abstract : Purpose of review: This review provides a summary of recent developments in classification of renal oncocytic neoplasms that were incorporated in the fifth edition WHO classification of renal tumors, released in 2022. Recent findings: Besides the distinct entities of renal oncocytoma and chromophobe renal cell carcinoma, the WHO now acknowledges a heterogeneous group of oncocytic tumors of the kidney that can be reported as 'oncocytic renal neoplasms of low malignant potential'. Case series by multiple institutions have revealed recurrent patterns of morphological features, protein marker expression, and genetic alterations within these neoplasms that may permit further subclassification in the future. Summary: The new classification system provides pathologists with the opportunity to simplify the diagnostic workup and reporting of morphologically equivocal oncocytic neoplasms.